2016
DOI: 10.1080/09603409.2016.1160501
|View full text |Cite
|
Sign up to set email alerts
|

Compositional effects on the cyclic oxidation resistance of conventional superalloys

Abstract: The 1100 °C cyclic oxidation performance of 25 Ni-base commercial and developmental alloys was compiled from an extensive database and ranked according to the 200 h weight change. Cyclic oxidation performance of superalloys is directly controlled by composition. These conventionally cast superalloys were composed of base elements [Ni-Co-Cr-Al], refractory elements [Nb-Mo-Ta-W], oxygen-active elements [Ti-Zr-Hf], light elements [B,C], and occasionally [V-Mn-Si], with P and S trace impurities. The oxidation resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 12 publications
(11 reference statements)
1
16
0
2
Order By: Relevance
“…Three types of possible preferential oxide layers could be expected for Ni-Cr-Al systems [9] oxides can be assumed according to EDS results. In literature, the presence of Cr 2 O 3 and NiCr 2 O 4 or also NiO is mainly discussed [31]. However, some studies also mentioned the presence of TiO 2 in the external oxide layer [31][32][33].…”
Section: Oxidationmentioning
confidence: 99%
“…Three types of possible preferential oxide layers could be expected for Ni-Cr-Al systems [9] oxides can be assumed according to EDS results. In literature, the presence of Cr 2 O 3 and NiCr 2 O 4 or also NiO is mainly discussed [31]. However, some studies also mentioned the presence of TiO 2 in the external oxide layer [31][32][33].…”
Section: Oxidationmentioning
confidence: 99%
“…Smialek and Bonacuse [ 13 ] studied 25 commercial superalloys subjected to cyclic oxidation tests at 1100°C for 200 cycles of 1 h. In these test conditions, MAR‐M246 superalloy showed a variation in mass per unit area equal to −24.44 mg/cm 2 , ranking 11th (in decreasing order) among the 25 studied alloys. For comparison, MAR‐M247 was the 6th losing just −4.22 mg/cm 2, and MAR‐200(Hf) was the 17th with −89.8 mg/cm 2 .…”
Section: Introductionmentioning
confidence: 99%
“…It was found that most of the studies reported in the literature involved cyclic oxidation tests. However, according to Smialek and Bonacuse, [ 13 ] both isothermal and cyclic oxidation tests are essential to obtain a complete description of the degradation of nickel‐based superalloys at high temperatures and in oxidizing atmospheres. Thus, given the importance of studying the behavior of superalloys in isothermal conditions and the paucity of works in the literature in these situations, this study aimed to evaluate the oxidation resistance of MAR‐M246 superalloy at high temperatures under isothermal conditions and to perform a microstructural characterization (SEM‐EDS and X‐ray diffraction [XRD]) of oxides under different conditions of time and temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, de acordo com as previsões desses autores, a superliga MAR-M246 atende o índice Al + 1/2Cr = 10 e portanto deve apresentar boa resistência à oxidação como uma liga à base de Ni-Cr-Al (SMIALEK;G.H.MEIER, 1987). Em geral, o comportamento de oxidação observado para MAR-M246 modificado está de acordo com as previsões empíricas realizadas por Smialek , Bonacuse, Sims e Stolloff (SMIALEK;G.H.MEIER, 1987;BONACUSE, 2016).…”
Section: 3unclassified
“…A boa resistência em geral à oxidação das duas ligas investigadas neste trabalho está principalmente relacionada à formação de óxidos protetores como Cr2O3 e Al2O3 (SMIALEK; BONACUSE, 2016) . A formação desses óxidos está diretamente influenciada pela quantidade de Cr e Al presente na liga, bem como pela contribuição dos outros elementos de liga.…”
Section: 3unclassified